Religion and Prejudice: Lessons Not Learned From the Past - Gorsuch, Richard L. (The international journal for the psychology of religion, 1993)
Altemeyer and Hunsberger (1992) analyzed fundamentalism and prejudice. Unfortunately, their article failed to provide data on several issues that past literature has established as crucial. The use of denominational affiliation, the failure to include intrinsic and extrinsic scales, and the failure to recognize the interaction of different value positions among Christian groups with other religious variables limits the interpretability of the results and thus the major conclusions that the authors attempt to draw.